Pengaruh Penggunaan Media Sosial Terhadap Ragam Bahasa Mahasiswa Akademi Refraksi Optisi Padang - Amril, Khairalfi Jumanisa; Saunir, Ihsan (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2026)
The development of social media has influenced students’ communication patterns, including their use of language varieties. The intensity of interaction in digital spaces encourages the emergence of non-standard language, abbreviations, and code-mixing, which tend to carry over into academic contexts. This study aims to analyze the effect of social media use on the language varieties of students at the Padang Academy of Refraction Optician as a vocational institution in the health sector. The study employed a quantitative approach using a survey method involving 80 students who actively use social media. Data were collected through questionnaires and analyzed using descriptive statistics and simple linear regression. The results indicate that social media use has a significant effect on students’ language varieties, with a significance value of 0.000 (p < 0.05) and a coefficient of determination (R²) of 0.40. These findings show that 40% of the variation in students’ language varieties is influenced by social media use, with an increased tendency toward the use of non-standard language, abbreviations, and code-mixing in academic communication. This study provides empirical contributions to strengthening language literacy and fostering academic and professional communication among students in the digital era.